Comparison of three facebow/semi-adjustable articulator systems for planning orthognathic surgery - A. M. O’Malley, A. Milosevic (Blackwell Synergy, 2000)
Articulators are of interest to the joint maxillofacial and orthodontic team as they facilitate the planning of combined orthodontic treatment and orthognathic surgery.